Study on sustainable livelihoods of fishers from Chalan beel, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
An assessment was carried out to observe the impacts of fish sanctuary on the livelihoods from fishers of Ruhul beel and Bamonji beel under Chalan beel in Pabna district of Bangladesh. Data were collected from selected sanctuary sites with prepared and pretested questionnaire and analyzed through statistical tests like ANOVA (Analysis of Variance), regression, correlation, Chi-square were used to identify the relationships between variables and significant differences/association among them. From physical capital point of view, it was found that 91.3% of fishermen’s houses were katcha, 6.52% were semi-pacca, and only 2.17% were pucca in case of Ruhul beel and in case of Bamonji beel 90.54% of fishermen’s houses were katcha, 8.11% were semi-pacca, and only 1.35% were pacca. There was no significant variation (ANOVA; P>0.05, Chi Square test; non-significant at 0.05 level) among the residences by well-being. From human capital, average age of the household heads (HHH) was 37.95(±) 1.354 for Ruhul beel respectively, whereas for Bamonji beel the average age were 38.05(±) 1.064. The medium aged group fishermen were dominant in Ruhul beel than Bamonji beel. There were no significant difference (P>0.05) found between the age groups by well-being. From income capital it was observed highest part of income were come from fishing contributing 64.89% (653.72±128.82 US$), 43.58% (431.89±74.66 US$) for Ruhul beel and Bamonji beel respectively. As per as natural and social capital, average used land holding was 0.274±0.136 ranging 0.065 ha to 0.534 ha for Ruhul beel and 0.228±0.305 ha ranging 0.040 to 0.267 ha for Bamonji beel. The average land holdings did not vary significantly (P>0.05) between the sites.Asian Australas. J. Biosci. Biotechnol. 2020, 5 (3), 100-114